Islamic Religious Education in the National Education System: Opportunities and Challenges for Character Building - Mubarak, Muhammad Syauqi; Fauzi, Muhammad Ridwan (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
This research aims to provide an in-depth understanding of the concept of Islamic Religious Education (PAI) in the context of Indonesia's national education system. It analyzes the role of PAI in shaping the character, morals, and spirituality of students to produce individuals who are devout, pious, and possess noble character. Using a qualitative case study approach, data was collected through interviews, direct observation, and analysis of relevant documents. The findings highlight that although PAI plays a crucial role in character development, there are challenges such as limited instructional time, lack of interest from students, and a disconnect between religious and general education. The study suggests reforming PAI through innovative teaching strategies, increased family support, and professional development for teachers. The research concludes that PAI has significant potential to contribute to character education in Indonesia, forming morally sound individuals who contribute positively to society. Penelitian ini bertujuan untuk memberikan pemahaman mendalam mengenai konsep Pendidikan Agama Islam (PAI) dalam konteks sistem pendidikan nasional Indonesia. Penelitian ini menganalisis peran PAI dalam membentuk karakter, moral, dan spiritual siswa untuk menghasilkan individu yang beriman, bertakwa, dan berakhlak mulia. Menggunakan pendekatan kualitatif dengan studi kasus, data dikumpulkan melalui wawancara, observasi langsung, dan analisis dokumen terkait. Hasil penelitian menunjukkan bahwa meskipun PAI berperan penting dalam pengembangan karakter, terdapat tantangan seperti keterbatasan waktu pengajaran, rendahnya minat siswa, dan ketidakselarasan antara pendidikan agama dan umum. Penelitian ini menyarankan reformasi PAI melalui strategi pembelajaran inovatif, peningkatan dukungan keluarga, dan pengembangan profesionalisme guru. Penelitian menyimpulkan bahwa PAI memiliki potensi besar dalam pendidikan karakter di Indonesia, membentuk individu yang berakhlak baik dan berkontribusi positif bagi masyarakat.